AC-DC Solid-State Conversion and Power Factor Correction using Thyristor-Based Static Var Compensator - Udo, E. U.; Oborkhale, L. I.; Nwaogu, C. C.; Amadi, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This paper presents AC-DC solid states converters with thyristor-based static Var compensator in power factor correction. There is need for solid-state ac–dc converters to improve power quality in terms of power factor correction, reduce total harmonic distortion at input ac mains and precisely regulate dc output. AC-DC converters operating in continuous-conduction mode have become popular because of reduced electromagnetic interference levels resulting from their utilization. The method employs the principle of interleaved converters, as it can be extended to a generic number of legs per winding of the autotransformers and high-power levels. The practical analysis of the converter is then plotted using a Simulink model of Matlab while a comparison of power factor and efficiency with relative to the load is drawn with Steady-State and Dynamic Performance of the Static Var Compensator (SVC). An experimental prototype load varied between 400W to 1 KW is implemented to validate the work. The results obtained indicates that when the output loads were 53KW, 135KW, 270KW, 470KW and 900KW, the efficiency were 55%, 70%, 80%, 90% and 97% respectively. These results confirmed that there was improvement in the power factor and efficiency with increase in the load.